The impact of weight loss on renal function in individuals with obesity and type 2 diabetes: a comprehensive review - Gong, Xuemei; Zeng, Xiaoxi; Fu, Ping (Frontiers in Endocrinology, 2024)
Obesity and Type 2 Diabetes (T2D) are two highly prevalent diseases that exhibit a complex interplay between them. Obesity serves as a primary risk factor for the development of T2D, and conversely, individuals with T2D often exhibit comorbid obesity. Renal dysfunction emerges as a critical consequence of the convergence of obesity and Type 2 Diabetes, contributing significantly to the overall burden of complications associated with these conditions. Recognizing the profound implications of renal dysfunction in individuals contending with both obesity and Type 2 Diabetes, interventions targeting weight loss have gained prominence as potential therapeutic avenues. Weight loss not only addresses the primary risk factor of obesity but also holds the promise of mitigating the progression of Type 2 Diabetes and its associated renal complications. This comprehensive review aims to explore the impact of weight loss on renal function in individuals contending with the convergence of obesity and T2D.